I Have My Own Standards: Positive Body Image Among Early Adult K-Pop Fans - Adventa, Claudia; Arianti, Rudangta (Jurnal Bimbingan dan Konseling Terapan, 2024)
In recent years, K-Pop has become a global sensation, especially in Indonesia, where it has a massive fan base on social media. While K-Pop brings joy to many, it has also raised concerns about its impact on body image, especially among young fans known as K-Popers. This study explores how young women who are fans of K-Pop feel about their bodies. Through interviews and observations, three participants—Yerin, Joy, and Rose—shared their thoughts. Despite K-Pop's influence on beauty standards, these women have a positive body image. They feel good about themselves and focus on self-confidence rather than what others think. Their stories show how they navigate societal pressures and find acceptance for their bodies. By prioritizing self-esteem and support from friends, they maintain a positive outlook despite external beauty ideals. This research sheds light on how K-Pop fans view their bodies and offers insights into promoting body positivity. It's important for researchers and others to continue exploring these issues to create a more accepting environment for everyone to feel good about themselves.